Study on the Relationship between the Fluidity of Paste in Stope and the Rheological Properties of Paste - Liang Wang; DengPan Qiao; JinCheng Xie; Jun Wang; Fei Huang (Advances in Civil Engineering)
Paste should be kept in homogeneous state without segregation or weak segregation during pipeline transportation, which can reduce the occurrence of pipe blockage accidents in engineering application. Only when the paste is homogeneous can the paste have good stope fluidity, and the stope fluidity is also restricted by the geometric size of the stope and other factors. Therefore, it is very important to study the homogeneity of paste and analyze the influence of paste rheological characteristics on stope fluidity. In this paper, it is pointed out that the vertical settling velocity of solid phase materials in paste in the liquid-phase dense medium is the main factor affecting the homogeneity of paste. Increasing the plastic viscosity and yield stress of the liquid-phase dense medium is beneficial to increase the drag force of aggregate and then reduce the settling speed of aggregate in the liquid-phase dense medium. On this basis, the homogeneity of paste can be judged. In the simplified paste flow field, using Cauchy stress equation and flow boundary conditions, the relationship between paste stope flow performance and paste rheological properties was analyzed, and the relationship model between the slope angle of paste flow formation and paste rheological properties was established. Compared with the experimental results, the error of the model results is small, and the slope angle of paste flow can be well predicted.